Effects of Dietary Plasticity and Landscape Heterogeneity on Brown Bears - Stutzman, Lindsey (Scholars Junction, 2017)
The brown bear (Ursus arctos) is a generalist omnivore that occupies diverse habitats and displays high levels of behavioral plasticity. Plasticity in foraging behavior can result in variable diets across a population, and allow individuals to use a greater variety of resources. The distribution of food in space and time may also be an important factor in determining brown bear resource selection as it can greatly influence foraging efficiency. Our objectives were to determine if seasonal brown bear home ranges were influenced by temporal availability and spatial distribution of resources and if deviation from an optimal diet influenced brown bear body condition. Understanding how the spatial and temporal distribution of food influences brown bear space use and the relationships between behavioral plasticity and the ability of populations to persist in dynamic environments could provide additional insights into the eco-evolutionary advantages of variable foraging behavior and ultimately population resilience.